The off-screen : an investigation of the cinematic frame - Peretz, Eyal, 1968- (Meridian (Stanford, Calif.), 2017)
By focusing on what is outside the frame, this book offers a comprehensive theory of film, a concise history of American cinema, and a reflection on the place and significance of film within the arts of modernity in general.